2020
DOI: 10.1111/sms.13847
|View full text |Cite
|
Sign up to set email alerts
|

Physical fitness development in relation to changes in body composition and physical activity in adolescence

Abstract: The decline in adolescents' physical fitness (PF) in recent decades has raised concerns about current population's possible future challenges with health and physical functional capacity. This study explored the associations between body composition, physical activity, maturation, and PF development in adolescents. Furthermore, PF development of adolescents with low initial PF was assessed. A 2-year observational study was conducted between spring 2013 and 2015. Nine comprehensive schools and their 10-to 13-ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 26 publications
2
17
0
3
Order By: Relevance
“…Similarly, the prevalence of low cardiorespiratory fitness between participants with WHtR equals or higher than 0.5 was 48.6% and 16.9% in boys and girls respectively, but only of 19.1% and 9.3% in boys and girls with WHtR lower than 0.5. Therefore, these results suggest a relatively high prevalence of low cardiorespiratory fitness between children with unhealthy body composition, especially in the case of boys, supporting the influence of fat mass on the development of cardiorespiratory fitness recently reported (Joensuu et al, 2020). The analysis of this tendency is out of the scope of the current paper but should be addressed in future studies.…”
Section: Discussionsupporting
confidence: 77%
“…Similarly, the prevalence of low cardiorespiratory fitness between participants with WHtR equals or higher than 0.5 was 48.6% and 16.9% in boys and girls respectively, but only of 19.1% and 9.3% in boys and girls with WHtR lower than 0.5. Therefore, these results suggest a relatively high prevalence of low cardiorespiratory fitness between children with unhealthy body composition, especially in the case of boys, supporting the influence of fat mass on the development of cardiorespiratory fitness recently reported (Joensuu et al, 2020). The analysis of this tendency is out of the scope of the current paper but should be addressed in future studies.…”
Section: Discussionsupporting
confidence: 77%
“…AL reflects the cumulative effect of stress in daily life, as a multi-system comprehensive index, it can be used as an early predictor of poor health or function. Our study found a correlation between AL and PA and outdoor time, which were generally consistent with emerging evidence from research on physical fitness development of adolescent [ 29 ], research on PA outdoor of college students suggesting that low level of PA and outdoor time could have an adverse effect on physical health and appeared to be associated with increased activation in the nervous, cardiometabolic and immune systems.…”
Section: Discussionsupporting
confidence: 90%
“…The review from Gorman S et al indicated that outdoor time could synergise with physical activity to prevent metabolic dysfunction, particularly that related to lifestyle diseases of obesity, type 2 diabetes and metabolic syndrome [ 27 ]. A series of new studies have shown that outdoor physical activity has varying degrees of impact on metabolism, cardiovascular and immune systems [ 28 , 29 ], which can be used as indirect evidence to support the effect of PA and outdoor time interaction on AL. In the meantime, our study provides further evidence of the positive interaction effect between low PA and low outdoor time on AL and produce the different degree influence to the organism each physiological system.…”
Section: Discussionmentioning
confidence: 99%
“…By following more than 600 young people from 2017 to 2019, this study also found that girls had greater difficulty maintaining or improving their PA level. The sex-related difference in the PA transition could be explained by physical development theory, which argues that a boy’s development increases his bone and muscle mass to facilitate PA, while puberty for a girl increases fat mass that reduces her ability to be physically active [ 50 ]. For Thai children and young people, the low participation of girls in PA is also culturally constructed, since most organized sports are geared more toward males.…”
Section: Discussionmentioning
confidence: 99%